Burial buildings of the 4th c. B.C. in Caria - Kisbali, Tamás (Actual Problems of Theory and History of Art, 2012)
The subject of this article is a group chamber tombs in Caria dating to the 4th c. B.C. They differ in shape and size but are connected by the use of corbelled or barrel vaults in the subterranean burial chamber. Some of them had overground structures. The Maussolleion at Halikarnassos is a continuation of this line, with a superstructure built in accordance with the wealth and demands of Maussollos.
Keywords: Hekatomnid Caria; Late Classic period; Asia Minor; ancient Caria; Maussolleion